Kamilla’s Letter to Aleksandra, or Not Just a Letter - Reda Griškaitė (Literatūra (Vilnius))
In this publication, the letter-manifesto of the writer Kamilla z Narbuttów Jurewiczowa (or Kamilla Narbuttówna vel Kamilla Narbutt, ~1815–1881), first published in 1852 in Vilnius, is presented. It explores the issues of gender equality, woman’s freedom(s) and powers, as well as questions of women’s education, which are closely related to the still-sensitive problem of a writing woman. Both the original letter-manifesto in Polish and its translation into Lithuanian (with subject-related commentaries) are provided to the reader.